PERUBAHAN KEBIJAKAN KERJASAMA INDONESIA-TIONGKOK PADA MASA PEMERINTAHAN JOKOWI (2014-2015) - Okta Sari; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This thesis describes the policy changes that occurred in the two leadership,in three periods of the reign of president rebuplik Indonesia 6th and 7th Susilo Bambang Yudhoyono (2004-2014) until Joko Widodo (2014-present). Where this cooperation include cooperation between the Republic of Indonesia and the Republic of China. In this case cooperation between the two countries that are in economic, political, trade, industry, tourism, culture etc.Those changes that occur that can impact in inside and outside the country. In the reign of Susilo Bambang Yudhoyono, Indonesia and China is a partner of a close cooperation relationship, but China is not yet a trading partner key to Indonesia, while during the reign of Joko Widodo, the state China has become the country's most influential and Indonesia is now highly dependent on this bamboo curtain country, so that today China is a major trading partner for Indonesia.Keywords: policy change, cooperation, Tiongkok